Bibliometric analysis of The Peruvian Journal of Gynecology and Obstetrics during the period 2018-2024 - Cabanillas-Lazo, Miguel (2024)
Objectives: To perform a bibliometric analysis of The Peruvian Journal of Gynecologyand Obstetrics (PJGO) during the period 2018-2024. Materials and methods:Bibliometric study in which all publications between 2018-2024 extracted from theScopus database were included. The number of publications, the most productiveinstitutions, the type of collaboration, the most productive countries, the mostcited articles and the authors with the highest academic production were used asbibliographic indicators. These were exported to the Scival and Bibliometrix 4.2.1 platform for analysis. VosViewer program (version 1.6.10) was used to evaluate co-citations between the PJGO and other journals indexed in Scopus. Results: A total of 397 papers published in the PJGO by 758 authors were collected, with a totalof 208 citations (0.53 citations per paper). Most of the publications had nationalcollaboration and single authorship (122 papers). The Universidad Nacional Mayorde San Marcos was the institution with the highest number of papers produced with88 articles. Regarding the country of affiliation Peru, Venezuela, Spain and Colombialed the list. Conclusions: The Peruvian Journal of Gynecology and Obstetrics is ajournal of Latin American relevance and with a growing national and internationalcollaboration in the field of reproductive health.